Blockchain Technology Immutability Framework Design in E-Government - Daelami Ahmad; Ninda Lutfiani; Alfian Dimas Ahsanul Rizki Ahmad; Untung Rahardja; Qurotul Aini (Universitas Medan Area, 2021)
This study was conducted to determine the capacity of Blokchain technology in recording transactions that occurred in the ledger and in general it also offer the government to be applied to the e-Government sector which can increase data transparency, avoid fraud, and increase public trust in the government. This problem also focused on the application, challenges in the future with respect to the allocation of Blockchain technology, and in the e-Government sector, the use of Blockchain technology did not appear to be the main focus therefore it needed deeper observational evidence for the use of Blokchain technology. In its application, the biggest challenges in utilizing blockchain were generally presented as innovations such as security, scalability, and flexibility. In order to approach this problem, theoretical references were used from pre-existing studies that discuss Blokchain technology, e-Government, public services, and the data were collected through indexed journals both on a national and international scale. And the review of this paper concluded that academic research in this sector had only just begun and the issues addressed in the literature were still very limited. Therefore, more intensive research in this area is still needed to advance this field of research academic research in this sector had only just begun and the issues addressed in the literature are still very limited.